Daily field checking list by Walter Rosene, March 4, 1934 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated March 4, 1934. This checklist was used by Walter Rosene to record birds sighted around Beaver Creek with Bob Walker between 7:30 and 10:00. Plustek--flatbed